2010
DOI: 10.1016/j.chembiol.2009.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Rhizocticins, Antifungal Phosphonate Oligopeptides Produced by Bacillus subtilis ATCC6633

Abstract: Summary Rhizocticins are phosphonate oligopeptide antibiotics containing the C-terminal non-proteinogenic amino acid (Z)-l-2-amino-5-phosphono-3-pentenoic acid (APPA). Here we report the identification and characterization of the rhizocticin biosynthetic gene cluster (rhi) in Bacillus subtilis ATCC6633. Rhizocticin B was heterologously produced in the non-producer strain Bacillus subtilis 168. A biosynthetic pathway is proposed based on bioinformatics analysis of the rhi genes. One of the steps during the bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 56 publications
0
103
0
Order By: Relevance
“…Bacillaene, difficidin and macrolactin are polyketides displaying a broad spectrum of antibacterial activities that may be involved in the biocontrol activity of the producing strain such as in the case of fire blight, a serious disease of orchard trees caused by Erwinia amylovora ). The phosphono-oligopeptide rhizocticin produced by B. subtilis also displays antifungal and nematicidal activities, but does not retain any bactericidal properties (Borisova et al, 2010). Peptide compounds represent the predominant class of Bacillus antibiotics.…”
Section: Direct Inhibition Of Phytopathogens 421 Antibiosis Membersmentioning
confidence: 99%
“…Bacillaene, difficidin and macrolactin are polyketides displaying a broad spectrum of antibacterial activities that may be involved in the biocontrol activity of the producing strain such as in the case of fire blight, a serious disease of orchard trees caused by Erwinia amylovora ). The phosphono-oligopeptide rhizocticin produced by B. subtilis also displays antifungal and nematicidal activities, but does not retain any bactericidal properties (Borisova et al, 2010). Peptide compounds represent the predominant class of Bacillus antibiotics.…”
Section: Direct Inhibition Of Phytopathogens 421 Antibiosis Membersmentioning
confidence: 99%
“…acute cystitis; FR-900098 and fosmidomycin, antimicrobials undergoing clinical trials for malaria; and phosphinothricin, the active component in several commercial herbicides (Liberty, Basta, and Rely). Second, the methodology needed for gene-based discovery of phosphonate biosynthetic loci has been rigorously established (17)(18)(19)(20)(21)(22)(23). This method relies on the fact that all but two characterized phosphonate biosynthetic pathways begin with the enzyme phosphoenolpyruvate (PEP) mutase (encoded by pepM) (14).…”
Section: Significancementioning
confidence: 99%
“…However, there are more reports on the biosynthesis of peptidic secondary metabolites involving nonribosomal peptide synthetase than reports describing Lals (26). Rhizocticin and phaseolotoxin are di-or tripeptide antibiotic and tripeptide phytotoxins, respectively, that contain an unusual amino acid, and two ATP-grasp enzymes were identified in each biosynthetic gene cluster (27,28). In rhizocticin biosynthesis, our results revealed that two Lals (RizA and RizB) combined three amino acids, yielding tripeptides similar to rhizocticin (19,20).…”
mentioning
confidence: 70%